SOME CONCEPTS OF HOMOMORPHISM AND ISOMORPHISM OF A GROUP - Zafar Murtozaqulov; Sayatjon Asilbayev (Bright Mind Publishing, 2025)
This article provides an in-depth analysis of the concepts of group homomorphism and isomorphism. A homomorphism is a special map that expresses the relationship between groups and allows algebraic structures to be connected. Isomorphism is defined as the complete equivalence of group structures, proving that they share the same structure. The article provides definitions, properties, and the mathematical significance of these concepts. Furthermore, various examples are given to illustrate their practical applications
Keywords: Group, homomorphism, isomorphism, algebra, kernel, image, bijectivity, injectivity, surjectivity.